Perbedaan Pengaruh BirthBall dan Hypnobirthing terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif - Tuti, Tuti; Ageng Septa Rini; Ratna Wulandari; Nurma Yunita; Delvi Kurniawati; Lidyaa Waasi'u Tri Yusleni Anggraini; Melita Dewi Saputri (2025)
Labor pain during the active phase of the first stage of labor is a major challenge that can affect both the comfort and progress of the birthing process. Non-pharmacological interventions such as the use of a birth ball and hypnobirthing techniques are widely employed as safe and effective alternatives for pain relief. This study aimed to analyze the effect of birth ball and hypnobirthing interventions on reducing labor pain during the active phase of the first stage of labor among mothers delivering at PMB Mira Dahlia, Toboali District, South Bangka Regency, in 2025. A quantitative study was conducted using a quasi-experimental design with a pre-test–post-test non-equivalent control group approach. A total of 46 respondents were selected through purposive sampling. Pain levels were measured using a combination of the Visual Analogue Scale and Wong-Baker Scale before and after the interventions. Data were analyzed using univariate and bivariate analysis with the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results showed a significant reduction in labor pain after the birth ball intervention, with all respondents experiencing decreased pain levels (Wilcoxon test p = 0.000; p < 0.05). The hypnobirthing intervention also resulted in a significant reduction in pain (Z = -4.260; p = 0.000). However, the Mann-Whitney test showed no significant difference in effectiveness between the birth ball and hypnobirthing interventions (p = 0.061 > 0.05), although the average pain reduction was greater in the birth ball group. It can be concluded that both birth ball and hypnobirthing interventions are effective in reducing labor pain during the active phase of the first stage of labor. While no significant difference was found between the two methods, birth ball showed a slightly higher average reduction in pain compared to hypnobirthing.